A User-Independent Successive Interference Cancellation Based Coding Scheme for the Unsourced Random Access Gaussian Channel - Vem, Avinash; Narayanan, Krishna R.; Chamberland, Jean-Francois; Cheng, Jun (IEEE transactions on communications, 2019)
This work introduces a novel coding paradigm for the unsourced multiple access channel model. The envisioned framework builds on a select few key components. First, the transmission period is partitioned into a sequence of sub-blocks, thereby yielding a slotted structure. Second, messages are split into two parts. A portion of the data is encoded using spreading sequences or codewords that are designed to be recovered by a compressed sensing type decoder. In addition to being an integral part of the data, the information bits associated with this first part also determine the parameters of the low-density parity check code employed during the subsequent stages of the communication process. The other portion of the message is encoded using the aforementioned low-density parity check code. The data embedded in this latter stage is decoded using a joint message passing algorithm designed for the T-user binary input real adder channel. Finally, devices repeat their codeword in multiple sub-blocks, with the transmission pattern being a deterministic function of message content independent of the identity of the device. When combined with successive interference cancellation, the ensuing communication infrastructure offers significant performance improvement compared to coding schemes recently published in the literature for unsourced random access.